Changes in ideal cardiovascular health among Iranian adolescents: 2007-2008 to 2015-2017 - Golaleh Asghari; Parvin Mirmiran; Alireza Rezaeemanesh; Maryam Mahdavi; Fereiodoun Azizi; Farzad Hadaegh (BMC, 2022)
Abstract Background Assessment of both behavior and factors of health as ideal cardiovascular health (iCVH) in adolescence could contribute to cardiovascular disease prevention in adulthood. Aims To explore the changes in the prevalence of iCVH and its components during a decade among Tehranian adolescents. Methods The 12-19 years old adolescents were selected from the Tehran Lipid and Glucose Study(TLGS). The iCVH score was calculated in the study period 1 (2007-2008; n = 267) and 2 (2015-2017; n = 336). To calculate iCVH, body mass index(BMI), systolic and diastolic blood pressure (BP), total cholesterol, fasting plasma glucose (FPG), physical activity, smoking status, and dietary intakes were measured by standard protocols. The changes in iCVH components between the two study periods were reported by prevalence (95% confidence interval). A logistic regression model was conducted to test the effects of study periods, sex, and age groups on the iCVH(≥ 6 scores). Results Overall, there was a reduction in the prevalence of ideal FPG (97.4 vs. 91.1%) and ideal BP(91.8 vs. 82.7%). Girls had a decrease in the prevalence of ideal BP(91.2 vs. 79.4%) as well as an increase in non-smoking status(77.6 vs. 89.7%). However, the prevalence of ideal FPG (96.5 vs. 88.5%) and ideal BP(92.2 vs 85.0%) decreased in boys. Study period 2, compared to period 1 was associated with lower odds of having iCVH. Furthermore, boys were 1.57 folds more likely to have ideal CVH factors than girls. Conclusion There was a decrease in the prevalence of ideal CVD metrics, including FPG and BP, after one decade. Generally, adolescent boys had higher odds of having ideal CVH compared to girls.